WE DIDN’T INHERIT OUR FATHERS’ LAND; WE BORROWED IT FROM OUR CHILDREN - Zavyalova, N.E.; Korlyakov, K.N. (Perm Federal Research Centre Journal, 2016)
The influence of different technology methods (crop rotations, crops set, lime and fertilizers application, soil management) on humus soil content, its dynamics and fractional composition, correlation between crops yields and soil fertility were studied in Perm Agricultural Research Institute in long-term stationary experiment.The results of research work fulfilled in 1971-2014 showed the trends in humus and organic matter general content and their fractional composition. Minimal permissible and optimal concentrations of humus mobile fraction in sod-podzolic soil were determined. Complex technique preventing not only soil degradation, but also promoting their stable fertility improvement, crops yields raising and agrolandscapes constant functioning was elaborated.